Maxim’s responsibilities toward food and bike delivery drivers under Law No. 6 Of 2023 (A study in Banda Aceh) - Teuku Hasbulhadi; Arifin Abdullah; Mustem Mustem (Priviet Social Sciences Journal, 2026)
The emergence of platform-based business models has significantly transformed conventional patterns of employment, raising ongoing debate regarding the legal status of individuals engaged through digital platforms within Indonesia's employment law framework. This study examines the legal responsibility of Maxim, a Russia-based digital transportation and food delivery platform operating in Banda Aceh, in light of Law Number 6 of 2023 on Job Creation. The research employs a normative-empirical juridical approach supported by in-depth interviews with five active Maxim drivers. The analysis is grounded in employment relationship theory, the concept of algorithmic subordination, and principles of labor protection viewed through the lens of social justice. The findings indicate that the three essential components of an employment relationship—namely work, wages, and subordination—are substantively reflected in the legal relationship between Maxim and its drivers, despite the company's formal designation of drivers as "partners" under its standard contractual arrangement. In practice, algorithmic control is exercised through order allocation systems, customer rating mechanisms, and unilateral account suspension policies. Collectively, these features create a level of functional subordination that closely resembles the characteristics of a conventional employment relationship. From the perspective of labor protection, the study reveals several significant concerns. None of the interviewed drivers received BPJS Ketenagakerjaan (Workers' Social Security) coverage financed by Maxim. Moreover, two out of the five drivers who experienced work-related accidents were required to bear their medical expenses independently, while only one driver received a discretionary Holiday Bonus (BHR) instead of the statutory Holiday Allowance (THR). Based on these findings, the study concludes that the designation of drivers as "partners" cannot be relied upon as a legal basis for exempting Maxim from its obligations under Law Number 6 of 2023. Accordingly, this research recommends the establishment of a hybrid legal framework specifically intended to regulate and protect digital platform workers in Indonesia.